The impact of gasoline emission on plants – a review. Issue 4 (20th April 2016) - Saxena, Pallavi; Kulshrestha, Umesh Chandra
ABSTRACT: This review presents the status of knowledge about gasoline exhaust pollution and its impact biochemical and physiological characteristics of plants. Parameters on such as leaf conductance, membrane permeability, ascorbic acid, chlorophyll and relative water content have been used as indicators to assess the impact of gasoline exhaust pollution on plant health. Tolerant plants such as Mangifera indica Linn. are reported showing an insignificant decrease in the percentage of chlorophyll content (3.6%) and a significant increase in the percentage of ascorbic acid (84.6%) and sensitive plants such as Cassia fistula are reported showing a significant decrease in the percentage of chlorophyll (66.4%) as well as ascorbic acid (32.9%). In the case of ornamental plants, Dracaena deremensis has been reported to show an insignificant decrease in the chlorophyll content but a significant increase in the ascorbic acid, pH and relative water content, which were found to be in tolerant category, while Dianthus caryophyllus showed sensitive characteristics. Such plants can be used as sinks and bioindicators for gasoline exhaust pollution. Though several studies reported biochemical impacts of individual or combined exhaust gases on plant species, the cumulative effect of gasoline exhaust on plant species has not been studied extensively, especially in the developing countries.